First report of botryosphaeriaceous fungi causing canker on Cedrela fissilis and leaf spots on Cariniana estrellensis in forest nursery in Brazil. Issue 4 (20th May 2016) - Lisboa, D. O.; Silva, M. A.; Machado, A. R.; Pinho, D. B.; Borges, L. S.; Pereira, O. L.; Furtado, G. Q.
Summary: Cariniana estrellensis and Cedrela fissilis are native forest species from Brazil that are widely used for arborization of parks and recuperation of degraded areas. The production of seedlings from these two forest trees in nurseries is severely affected by fungal diseases. Morphological identification, sequencing analysis of three gene regions (TEF+ACT+ITS or TEF+TUB2 + ITS) and pathogenicity tests confirmed that fungi belonging to Botryosphaeriales are the aetiological agent of the diseases. This is the first report of Phyllosticta capitalensis causing leaf spots on C. estrellensis and Botryosphaeria dothidea causing canker on C. fissilis in forest nurseries in Brazil.